CRITICAL REVIEW ON INSTITUTIONAL REAL ESTATE INVESTMENT DECISION-MAKING MODELS - Aziz, Fatin; Mohd Adnan , Yasmin; Ahmad Baharum , Zarita; MOHD FOUDZY, Noorame (Journal of Surveying, Construction and Property, 2024)
This critical review delves into the underexplored realm of institutional real estate investment decision-making, a domain that holds paramount significance in the financial landscape. Despite the extensive scrutiny of individual real estate investors’ decision-making processes, there exists a noticeable lack of research on the pivotal role played by institutional investors. As the primary stakeholders armed with substantial financial resources, institutional investors, encompassing entities such as investment funds, insurance companies, and pension funds, wield unparalleled influence in the market. This paper aims to unravel the complex decision-making models employed by institutional investors, focusing on the period from 2000 to 2024. Employing the PRISMA model, the review meticulously incorporates 21 pertinent articles, and a comprehensive thematic analysis, facilitated by ATLAS.ti version 23.2.1, reveals three prominent decision-making models – the Normative Model, the Descriptive Model, and the Prescriptive Model. In dissecting the factors that shape institutional real estate investment, the study identifies four key influencers: political, economic, legal, and real estate market fundamentals. The intricate interplay of these factors forms the crux of decision-making strategies adopted by institutional investors, as they diligently safeguard the interests of their trustees. Moreover, a noteworthy revelation surfaces regarding the geographical bias in existing research, with a scarcity of studies in developing countries, notably in Malaysia. This observation not only underscores the need for more comprehensive exploration in these regions but also presents a compelling avenue for future research endeavors. This critical review not only contributes to the ongoing discourse but also paves the way for a more nuanced understanding of the dynamic landscape of institutional real estate investment decision-making.